Користь від VoLTE та VoWiFi в сучасному житті - Сипков, І. А. (ХНУРЕ, 2025)
This work is devoted to analyzing the benefits of Voice over LTE (VoLTE) and Voice over Wi-Fi (VoWiFi) technologies in modern communication. The study examines their impact on call quality, network efficiency, and user experience. A comparison of VoLTE and VoWiFi with traditional voice communication methods is conducted, highlighting their advantages in terms of coverage, sound clarity, and reliability. It is concluded that VoLTE and VoWiFi significantly improve telecommunication services, especially in areas with weak cellular coverage or high network congestion.
Keywords: VoLTE; VoWiFi